Pre-ischemic Lactate Levels Affect Post-ischemic Recovery in an Isolated Rat Heart Model of Donation After Circulatory Death (DCD) - Arnold, Maria; Segiser, Adrian; Graf, Selianne; Méndez-Carmona, Natalia; Sanz, Maria N.; Wyss, Rahel K.; Kalbermatter, Nina; Keller, Nino; Carrel, Thierry; Longnus, Sarah (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Donation after circulatory death (DCD) could substantially improve donor heart availability. In DCD, the heart is not only exposed to a period of warm ischemia, but also to a damaging pre-ischemic phase. We hypothesized that DCD-relevant pre-ischemic lactate levels negatively affect post-ischemic functional and mitochondrial recovery in an isolated rat heart model of DCD. Methods: Isolated, working rat hearts underwent 28.5’ global ischemia and 60’ reperfusion. Prior to ischemia, hearts were perfused with one of three pre-ischemic lactate levels: no lactate (0 Lac), physiologic lactate (0.5mM; 0.5 Lac), or DCD-relevant lactate (1mM; 1 Lac). In a fourth group, an inhibitor of the mitochondrial calcium uniporter was added in reperfusion to 1 Lac hearts (1 Lac+Ru360). Results: During reperfusion, left ventricular work (heart rate–developed pressure product) was significantly greater in 0.5 Lac hearts compared to 0 Lac or 1 Lac. In 1 Lac vs 0.5 Lac hearts, in parallel with decreased function, cellular and mitochondrial damage was greater, tissue calcium content tended to increase, while oxidative stress damage tended to decrease. The addition of Ru360 to 1 Lac hearts partially abrogated the negative effects of DCD-relevant pre-ischemic lactate levels (greater post-ischemic left ventricular work and less cytochrome c release in 1 Lac+Ru360 vs 1 Lac). Conclusion: DCD-relevant levels of pre-ischemic lactate (1mM) reduce contractile, cellular and mitochondrial recovery during reperfusion compared to physiologic levels. Inhibition of mitochondrial calcium uptake during early reperfusion improves post-ischemic recovery of 1 Lac hearts, indicating calcium overload as a potential therapeutic reperfusion target for DCD hearts.